Viscous flow between two sinusoidally deforming curved concentric tubes: advances in endoscopy - L. B. McCash (Nature Portfolio, 2021)
Abstract Viscous flow between two sinusoidally deforming curved concentric tubes is mathematically investigated for the first time. Exact solutions are computed to analyse the flow between these two tubes and graphical outcomes are included for a thorough analysis of the solutions. The present article has prime applications in endoscopy as a novel peristaltic endoscope is introduced first time for a curved sinusoidal tube. This curved nature of outer sinusoidal tube with a flexible peristaltic endoscope placed inside it covers the topic of practical applications like endoscopy of human organs having curved shapes and the maintenance of complex machineries that involve complex curve structures. The usage of a flexible peristaltic endoscope inside a curved sinusoidal tube makes the process of catheterization more comfortable.